2018
DOI: 10.1093/rheumatology/kex522
|View full text |Cite
|
Sign up to set email alerts
|

What is new in pain modification in osteoarthritis?

Abstract: There is a big need for the development of novel therapies for the safe management of chronic pain associated with OA. Here we reviewed PubMed (2015 onward) and ClinicalTrials.gov for ongoing and recently completed trials where pain in OA is the primary outcome measure. Three broad categories were identified: biological therapies, small molecules and cryoneurolysis. The most promising new strategy is blockade of nerve growth factor with antibodies. Two anti-nerve growth factor antibodies, tanuzemab and fasinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
11

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 62 publications
1
32
0
11
Order By: Relevance
“…C3 may be an important factor in the pathogenesis of OA clinical symptoms. Targeting C3 could be a potential therapy to address an unmet need to develop novel therapies for the safe management of chronic pain associated with OA . In vivo animal models have shown that whole body knockout of C3 ameliorated experimental arthritis in mice .…”
Section: Discussionmentioning
confidence: 99%
“…C3 may be an important factor in the pathogenesis of OA clinical symptoms. Targeting C3 could be a potential therapy to address an unmet need to develop novel therapies for the safe management of chronic pain associated with OA . In vivo animal models have shown that whole body knockout of C3 ameliorated experimental arthritis in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Für eine Sensibilisierung verantwortlich sind in der Regel Entzündungsmediatoren (z. B. Prostaglandine, Neuropeptide oder Zytokine) oder Neurotrophine aus dem umliegenden Gewebe [1][2][3][4][5]. Über Rezeptoren in der Nozizeptormembran aktivieren diese Mediatoren Second messenger-Wege in den Nervenzellen und damit assoziierte Proteinkinasen, welche daraufhin Ionenkanäle phosphorylieren (s.u.).…”
Section: Sensibilisierung Von Gelenknozizeptoren Bei Entzündungunclassified
“…Seine Rolle bei der Transduktion von Reizen im Gelenk ist jedoch noch unzureichend geklärt. Eine neuere klinische Studie zeigte, dass die intraartikuläre Applikation eines synthetischen Capsaicins, welches speziell den TRPV1 adressiert, zu einer reversiblen Deaktivierung von Nozizeptoren im Gelenk führt [1].…”
Section: Sensibilisierung Von Gelenknozizeptoren Bei Entzündungunclassified
See 1 more Smart Citation
“…Current OA treatments include a combination of non-pharmacological and pharmacological interventions 4 that follow a multimodal stepwise approach 5 . Despite recent advances in research and available therapies, there remain large unmet medical needs in this field 6 . In particular, a better understanding of the different OA phenotypes and patient-tailored therapies are needed 7 .…”
Section: Introductionmentioning
confidence: 99%